Professional development, reflection and decision-making - Jasper, Melanie (Vital notes for nurses., 2006)
Vital Notes for Nurses: Professional Development, Reflection and Decision-making provides a concise, accessible introduction to professional development, reflective practice and clinical decision-making. Vital Notes for Nurses: Professional Development, Reflection and Decision-making explores the core strategies of reflective practice and decision-making underlying professional nursing development. Separate chapters on reflective writing, evidence-based practice, clinical supervision and portfolios demonstrate the inter-relationship between professional development and professional practice. It.